Kerancuan dalam bahasa Melayu (Jurnal Bahasa, 2006)
This article discusses the disorderly usage found currently in the Malay language, in the official/formal domain, as examined from various positions. Among the more important ones are (a) usage that does not give prominence to the grammar rules of the standard variety of the Malay language, (b) habit of intermingling with the English language when using the Malay language, and (c) practice of using the English language as a vehicle language to replace the Malay language. Impli-cations of these disorderly practices on the Malay language as the national and official language of the nations, are also examined, par-ticularly in the context of nation building from the cultural dimension. Measures and actions to be taken to halt these corrupt usages consti-tute another important discussion in the article.